Market Structure and Market Access - Francois, Joseph; Wooton, Ian (World Bank, Washington, DC, 2012)
The authors examine an issue at the nexus of domestic competition policy and international trade, the interaction between goods trade and market power in domestic trade and distribution sectors. Theory suggests a set of linkages between service-sector competition and goods trade supported by econometrics involving imports of 22 OECD countries compared with 69 exporters. Competition in services affects the volume of goods trade. Additionally, because of interaction between tariffs and competition, the market structure of the domestic service sector becomes increasingly important as tariffs are reduced. Empirically service competition apparently matters most for exporters in smaller, poorer countries. The results also suggest that while negotiated agreements leading to cross-border services liberalization may boost goods trade as well, they may also lead to a fall in goods trade when such liberalization involves foreign direct investment leading to increased service sector concentration.